Estimativas de (Co)Variâncias entre Características de Reprodução e de Crescimento em Fêmeas de um Rebanho Nelore - Mercadante, Maria Eugênia Zerlotti; Lôbo, Raysildo Barbosa; De Oliveira, Henrique Nunes [UNESP] (My University, 2000)
Informations of 7986 births of animals from a Nellore cattle herd, from 1960 to 1993, were used to estimate (co) variance components, heritabilities and genetic correlations of weaning weight (W240), yearling weight (W365), age at first calving (AFC), first calving interval (CII), reproductive efficiency (RE), longevity (LONG), calculated as years of permanence of cow in herd and weaning weight of the first calf of cow (W240C). The analysis were performed using the MTDFREML software, estimating the (co) variance components by restricted maximum likelihood, assuming an animal model. Estimates of heritability showed similar results among the different analyses, being higher (0.26 to 0.35) for W240, W365 and AFC and lower (0.08 to 0.26) for CII, RE, LONG and W240C. In general, the estimates of genetic and phenotypic correlations among growth and reproductive traits were low and among the reproductive traits were high and favorable. Some correlations between maternal genetic effect of the growth and the direct genetic effect of the reproductive traits were of average magnitude and unfavorable, suggesting genetic antagonism between milk production and reproduction.
Estimates of (Co)Variances among Reproductive and Growth Traits in Female Nellore Cattle
Keywords: Genetic parameters; Growth; Nellore breed; Reproduction; Zebu female